Proceedings of the 2005 IEEE International Conference on Robotics and Automation
DOI: 10.1109/robot.2005.1570172
|View full text |Cite
|
Sign up to set email alerts
|

Design and Control of a Variable Stiffness Actuator for Safe and Fast Physical Human/Robot Interaction

Abstract: This paper is concerned with the design and control of actuators for machines and robots physically interacting with humans, implementing criteria established in our previous work [1] on optimal mechanical-control co-design for intrinsically safe, yet performant machines. In our Variable Impedance Actuation (VIA) approach, actuators control in real-time both the reference position and the mechanical impedance of the moving parts in the machine in such a way to optimize performance while intrinsically guarantee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
273
0
5

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(279 citation statements)
references
References 11 publications
1
273
0
5
Order By: Relevance
“…On the other hand, the performance of the robot, including accuracy and rapidity, remains necessary as the task requirement [1]. Tonietti, et al [2] explain that the machines must be safe against all conceivable accidents whilst they interact with humans. Another important target is their behaviour, which can frequently be expressed as a speed of motion.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the performance of the robot, including accuracy and rapidity, remains necessary as the task requirement [1]. Tonietti, et al [2] explain that the machines must be safe against all conceivable accidents whilst they interact with humans. Another important target is their behaviour, which can frequently be expressed as a speed of motion.…”
Section: Introductionmentioning
confidence: 99%
“…Work on collision reaction control strategies has shown that switching to torque control with gravity compensation upon impact can greatly reduce the force exerted on the human in the event of a collision [9]. New types of actuators with variable impedance have been developed, and show great potential in allowing for intrinsically safer robots by reducing joint stiffness when the robot is moving quickly [10].…”
Section: Related Workmentioning
confidence: 99%
“…where τ k (q, u 1 , u 2 ) is given by (2). The details of the mechanical design used are presented in Sec.…”
Section: B Example: Mechanically Adjustable Compliance and Controllamentioning
confidence: 99%
“…In recent years, the robotics community has looked for inspiration in the capabilities of humans to design a generation of actuators that have variable impedance [1], [2], [3]. The benefits of such actuators include high dynamic range (e.g.…”
Section: Introductionmentioning
confidence: 99%